Physical activity in wheelchair-using youth with spina bifida: An observational study 11 Medical and Health Sciences 1117 Public Health and Health Services - Bloemen, Manon A.T.; Van Den Berg-Emons, Rita J.G.; Tuijt, Matthijs; Nooijen, Carla F.J.; Takken, Tim; Backx, Frank J.G.; Vos, Marleen; De Groot, Janke F. (BioMed Central Ltd., 2019)
Background: Even though typically developing youth are already at risk for physical inactivity, youth with spina bifida may be even at higher risk as a consequence of their reduced mobility. No objective data is available for youth with spina bifida who use a manual wheelchair, so the seriousness of the problem is unknown. The purpose of this observational study was to quantify physical activity in wheelchair-using youth with spina bifida and evaluate the intensity of activities. Methods: Fifty-three children and adolescents (5-19 years) with spina bifida who use a manual wheelchair for daily life, long distances or sports were included. To assess time spent in several types of activities VitaMove data of 34 participants were used and were presented as time spent sedentary and time spent physically active. This was compared to reference data of typically developing youth. To assess time spent in several intensities Actiheart data of 36 participants were used. The intensities were categorized according to the American College of Sports Medicine, ranging from very light intensity to near to maximal intensity. Data of 25 participants were used to combine type of activity and intensity. Results: Children and adolescents with spina bifida who use a manual wheelchair were more sedentary (94.3% versus 78.0% per 24 h, p < 0.000) and less physically active (5.0% versus 12.2% per 24 h, p < 0.000) compared to typically developing peers. Physical activity during weekend days was worse compared to school days; 19% met the Guidelines of Physical Activity during school days and 8% during weekend days. The intensities per activity varied extensively between participants. Conclusions: Children and adolescents with spina bifida who use a manual wheelchair are less physically active and more sedentary than typically developing youth. The physical activity levels on school days seem to be more favorable than the physical activity levels on a weekend day. The low levels of physical activity need our attention in pediatric rehabilitation practice. The different intensities during activities indicate the importance of individually tailored assessments and interventions.
Keywords: Adolescents; Children; Physical activity; Spinal Dysraphism; Wheelchairs; Youth; Rehabilitation; Health Informatics